If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 = 122 + -10x Reorder the terms: 6 + 6x = 122 + -10x Solving 6 + 6x = 122 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 6 + 6x + 10x = 122 + -10x + 10x Combine like terms: 6x + 10x = 16x 6 + 16x = 122 + -10x + 10x Combine like terms: -10x + 10x = 0 6 + 16x = 122 + 0 6 + 16x = 122 Add '-6' to each side of the equation. 6 + -6 + 16x = 122 + -6 Combine like terms: 6 + -6 = 0 0 + 16x = 122 + -6 16x = 122 + -6 Combine like terms: 122 + -6 = 116 16x = 116 Divide each side by '16'. x = 7.25 Simplifying x = 7.25
| 11x+3=4(3x+4) | | -x^5-x^3+4x=0 | | 11x+3=4x(3x+4) | | -49-7x=9x+17 | | D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 |